Poscrise?: Relacins femininas en das curtametraxes da 'Nova Dispora Galega' - Barbour, Catherine (My University, 2026)
This article takes a feminist approach to the analysis of interpersonal conflicts between women in two short fictional films pertaining to the post-crisis cinema of the ‘New Galician Diaspora’. Drawing on Sara Ahmed’s theorisation of the ‘Promise of Happiness’ in her eponymous essay (2010) which critiques the supposed responsibility of migrants and minorities to be ‘happy’, it is argued that Illa Pedra (Stone Island) (2010) and Galicia. Portobello Road (2015) directed by Adriana Páramo Pérez (Vigo, 1985) expose the failure of neoliberal economics by challenging heteropatriarchal norms. Through exploration of the cinematographic portrayal of the complexity of women’s interpersonal relationships in contexts of return migration, the article examines how these films demonstrate the detrimental impact of economic crises on women’s lives, bodies and livelihoods.
PUBLISHED
Keywords: Identities in Transformation; Inclusive Society; EMIGRATION; Film and Gender; Galician Studies; Culture; Gender